A state-of-the-art review of N self-doped biochar development in supercapacitor applications - Xiaorui, Liu; Haiping, Yang (Frontiers in Energy Research, 2023)
Due to its renewability, eco-friendliness, and cost-effectiveness, biochar is a promising alternative to fossil fuel-based carbon for electrode material application in supercapacitors. However, pristine biochar often exhibits poor structure and low activity, which strongly inhibit its commercial utilization. N-doping is an efficient way to improve the electrochemical performance of biochar by enhancing the conductivity and surface wettability that further induce a pseudo-capacitance effect. Compared with external doping, the synthesis of N self-doped biochar from natural N-rich biomass without using external N precursors, which are harmful and costly, has attracted increasing attention. Few reviews of N-doped biochar applications in supercapacitors are available, and studies of N self-doped biochar are still scarce. This paper reviews the developments over the past 10 years on the preparation, activation, and application of N self-doped biochar in supercapacitors. Notably, the evolution of N-functionalities during N self-doped biochar production with or without activating agents was analyzed. The relationships between N content and the specific capacitance and the contribution of N self-doping-induced pseudo-capacitance to the total specific capacitance are also discussed. Finally, the challenges and the prospects of N self-doped biochar applications in supercapacitors are proposed.